2018
DOI: 10.1021/acs.orglett.8b01510
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chloro(phenyl)trifluoromethyliodane and Catalyst-Free Electrophilic Trifluoromethylations

Abstract: The present work deals with a challenge in the synthesis of aryltrifluoromethyliodanes (ArICFX) and develops a direct route to PhICFCl via a simple ligand-exchange reaction of PhI(OCOCF), MeSiCF, and NaCl for the first time. The I-Cl bond length in PhICFCl supports its iodonium character, which enables an enhanced CF-transfer capability in electrophilic S-, O-, N-, and C-trifluoromethylations as well as in catalyst-free trifluoromethylation-cyclizations of arylisonitriles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 62 publications
0
32
0
Order By: Relevance
“…The spontaneous formation of N ‐CF 3 nitrilium species was observed during our studies on the reactivity of PhICF 3 Cl. We found that PhICF 3 Cl slowly degraded in MeCN though in solid state, it exhibited complete air tolerance under ambient conditions [13b] . A product ( δ =−59 ppm) was detected in 71 % 19 F NMR yield after heating a mixture of PhICF 3 Cl and MeCN.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The spontaneous formation of N ‐CF 3 nitrilium species was observed during our studies on the reactivity of PhICF 3 Cl. We found that PhICF 3 Cl slowly degraded in MeCN though in solid state, it exhibited complete air tolerance under ambient conditions [13b] . A product ( δ =−59 ppm) was detected in 71 % 19 F NMR yield after heating a mixture of PhICF 3 Cl and MeCN.…”
Section: Resultsmentioning
confidence: 84%
“…Only one work included N ‐CF 3 acetonitrilium ion, which was generated in an acetonitrile solution of proton‐activated Togni's reagent and delivered N ‐CF 3 imidoyl derivatives after a nucleophilic trapping [11, 12] . During our ongoing efforts to develop new trifluoromethylations, [13] we prepared an externally coordinated CF 3 ‐containing λ 3 ‐iodane (PhICF 3 Cl) [13b] and developed it to be efficiently electrophilic CF 3 source [13] . By simply stirring PhICF 3 Cl in nitriles, we could detect N ‐CF 3 nitrilium derivatives in good yields recently.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Wang and coworkers reported the use of the CF 3 -containing λ 3 -iodane, PhICF 3 Cl [ 55 ], as a bifunctional reagent for the uncatalyzed chlorotrifluoromethylation of non-conjugated and conjugated alkenes [ 56 ]. This process was also successfully extended to biologically important molecules such as ibuprofen, indomethacin, estrone, and oxaprozin derivatives among others.…”
Section: Chloro- and Bromotrifluoromethylationmentioning
confidence: 99%
“…23 in MeCN. 24 Although the process was efficient and provided high yields (51-100%) of products, the scope remains narrow as only a few terminal alkynes (8 examples) were evaluated.…”
Section: Bifunctional Reagentsmentioning
confidence: 99%